Culture-Based Typography: The Creation of the Ringgit Bali Font as a Visual Representation of Traditional Balinese Ceremonial Offerings - Ida Bagus Putu Adi Pratama; I Putu Adi Natha; Putu Gede Wisnu Yasa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study explores the creation of the Ringgit Bali font, a typeface inspired by the visual elements of traditional Balinese ceremonial offerings, particularly Lamak. Employing a practice-based research approach, the study investigates how the aesthetic values and philosophical meanings embedded in Balinese culture can be translated into letterforms with distinctive characteristics. The research aims to uncover the visual potential of Lamak and adapt it into a type design that not only represents Balinese cultural identity but also serves diverse design applications, including branding, visual identity, and promotional media. The font development process involved form analysis of Lamak, typographic experimentation, and legibility testing to ensure that the resulting design possesses both artistic value and functional usability in visual communication design. Visual data of Lamak were collected through direct observation and documentation studies. The final outcomes of this research include the Ringgit Bali typeface and a documentation book detailing the font creation process, form exploration, and its application across various design contexts.